2009
DOI: 10.1161/circulationaha.109.852467
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Reduces the Development and Rupture of Experimental Aortic Aneurysms

Abstract: Background-Development and rupture of aortic aneurysms involve a combination of complex biological processes.Rosiglitazone, a peroxisome proliferator-activated receptor-␥ agonist, has been shown to have a broad spectrum of effects in vivo. The hypothesis that rosiglitazone would reduce aneurysm expansion or rupture was tested in the angiotensin II (Ang II)-induced hypercholesterolemic mouse model. Methods and Results-Apolipoprotein E-deficient mice, 12 months of age, were allocated to 4 groups. Three groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 39 publications
(41 reference statements)
3
88
1
1
Order By: Relevance
“…A recent study by Cassis et al ( 20 ) demonstrated that Ang II infusionpromoted AAA formation was independent of increases in blood pressure . Some other agents, like vitamin E and rosiglitazone, exhibited inhibitory effects on Ang II-induced AAA formation without altering the blood pressure ( 16,35 ). Moreover, the s-EH inhibitor AR9276 did not reduce blood pressure in this AAA model ( 14 ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A recent study by Cassis et al ( 20 ) demonstrated that Ang II infusionpromoted AAA formation was independent of increases in blood pressure . Some other agents, like vitamin E and rosiglitazone, exhibited inhibitory effects on Ang II-induced AAA formation without altering the blood pressure ( 16,35 ). Moreover, the s-EH inhibitor AR9276 did not reduce blood pressure in this AAA model ( 14 ).…”
Section: Discussionmentioning
confidence: 82%
“…EETs activate PPAR ␥ ( 15 ), and PPAR ␥ activation is associated with AAA development ( 16,44 ). Studies showed that VSMC PPAR ␥ deletion promotes AAA ( 44 ), and the administration of the PPAR ␥ agonist, rosiglitazone, prevents AAA progression ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-b-dependent changes during aneurysm development include increased expression and/or activities of matrix-degrading enzymes such as metalloproteinases, degradation of elastic fibers, enhanced proliferation and migration of VSMCs, and excessive collagen secretion and deposition (reviewed in Jones et al 2009). Overall, the effects of these alterations, which target both matrix degradation and matrix deposition, weaken the aortic wall rendering it more prone to dilatation, dissection, and rupture.…”
Section: Tgf-b Signaling In Vascular Homeostasismentioning
confidence: 99%
“…Rosiglitazone reduced aortic expansion and rupture in Ang II-infused ApoE -/-mice along with a suppression of Ang II type A receptor, TNFα, IL-6 and E-selectin. 90 Reduction of lesions in animals pretreated with rosiglitazone is concomitant with decreased expression of inflammatory mediators. Using transplantation of vessels from PPARγ knock-out mice, Hamblin et al demonstrated that loss of PPARγ in vascular SMCs promoted aortic dilatation and elastin degradation and identified cathepsin S as a target gene for PPARγ, suggesting PPARγ as an important contributor in attenuating the development of aortic aneurysms.…”
Section: Aneurysmmentioning
confidence: 99%